Prospective study of perinatal outcome in pregnancies with primary antiphospholipid syndrome - Ćetković, Aleksandar; Kastratović, Biljana; Novaković, Ivana (Vojnosanitetski pregled, 2014)
Background/Aim. Pregnancies complicated with antiphospholipd syndrome are associated with the increased perinatal mortality and morbidity. The aim of this study was to assess perinatal outcome in pregnancies with primary antiphospholipd syndrome. Methods. This prospective study evaluated perinatal outcome in 25 pregnant women with antiphospholipid syndrome. After establishing vital pregnancy all the patients were treated with low-molecular-weight heparin and aspirin. The perinatal outcome was measured by rates of miscarriages, preterm deliveries, live births and neonatal complications. Results. Of the 25 pregnancies, 20 (80%) resulted in live birth, 3 (12%) in spontaneous abortion and 2 (8%) were stillbirths. The mean gestational age at delivery was 37.2 ± 1.0 weeks, mean neonatal birth weight was 2,930.4 ± 428.0 g. Prematurity occurs in 4 (20%) live births, and there were 4 (20%) intrauterine growth restriction with mean birth weight 2,060 ± 210.6 g. Neonatal complications were present in 6 (30%) newborns. Adverse perinatal outcome was significantly associated with anticardiolipin IgG antibodies (p < 0.01) and development of hypertension during pregnancy (p < 0.01). Conclusion. Despite a high incidence of adverse perinatal outcomes in pregnancies with primary antiphospholipid syndrome, early treatment with aspirin and low-molecular-weight heparin, combined with meticulous fetomaternal monitoring could be associated with a relatively high probability of favorable perinatal outcome.